2019
DOI: 10.1155/2019/7898069
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation Evoked by Oxidative Stress Reduced Lens Epithelial Cell Antioxidant Functions by Increasing the Stability and Transcription of TP53INP1 in Age-Related Cataracts

Abstract: Oxidative stress plays an important role in the pathogenesis of cataracts. Small ubiquitin-like modifier (SUMO) proteins have great effects on cell stress response. Previous studies have shown that TP53INP1 can arrest cell growth and induce apoptosis by modulating p53 transcriptional activity and that both TP53INP1 and p53 are substrates of SUMOylation. However, no previous research has studied the effect of SUMOylation on the oxidative stress response in cataracts. This is the first study to investigate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Also, mutant Peroxiredoxin-6 at its SUMO1 sites could gain protective functions by maintaining its integrity and activity in epithelial cells of the aging human lens. Recently, SUMOylation has inspired an increasing number of researchers to explore the different target proteins and roles in the development of ocular disease treatments 24,52 . Currently, we focused on p48 PAX6 SUMOylation, including major sites, and SENP1-mediated de-SUMOylation improves the stability of PAX6 and amplifies the protective effects of PAX6 on corneal endothelial injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Also, mutant Peroxiredoxin-6 at its SUMO1 sites could gain protective functions by maintaining its integrity and activity in epithelial cells of the aging human lens. Recently, SUMOylation has inspired an increasing number of researchers to explore the different target proteins and roles in the development of ocular disease treatments 24,52 . Currently, we focused on p48 PAX6 SUMOylation, including major sites, and SENP1-mediated de-SUMOylation improves the stability of PAX6 and amplifies the protective effects of PAX6 on corneal endothelial injuries.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Studies have confirmed that cataracts are directly related to the apoptosis of LECs caused by oxygen free radicals. 6,7 Thus, it is important to explore antioxidant drugs that can prevent the formation and development of cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been revealed that antioxidant agents prevent the generation of free radicals that participate in the process of cataract formation (Chang et al, 2013;Abbas and Hussain, 2017). Exposure to environmental stresses (lead to elevated oxidative stress) threatens the eye health (Lu et al, 2019). Oxidative damage in the eye lens is responsible for many types of cataract (Varma et al, 2011).…”
Section: Discussionmentioning
confidence: 99%